Effect of Rejuvenators on the Workability and Performances of Reclaimed Asphalt Mixtures - Wei Tang (MDPI AG, 2021)
The use of rejuvenators has enhanced the workability of asphalt mixtures containing the reclaimed asphalt pavement (RAP). This conclusion is based on the determination of viscosity of asphalt binders, while not validated from reclaimed asphalt mixtures. In this study, the effect of two rejuvenators (ordinary and emulsified rejuvenator) on the workability of reclaimed asphalt mixtures was evaluated by measuring the mixing torque and determining the air void content of reclaimed mixtures. In addition, their effects on the performances of reclaimed mixture were studied via the three indexes tests, rutting test and freeze-thaw splitting tests. The experimental results show that mixing torque and air void content of reclaimed mixtures with the emulsified rejuvenator is 4% and 6% lower than that with the ordinary rejuvenator, respectively. This indicates that improvement of the workability of reclaimed mixtures can be achieved by using an emulsified rejuvenator, but not by an ordinary rejuvenator. That is also the reason that at least 20% greater high-temperature stability is found for reclaimed mixtures by using the emulsified rejuvenator than using the ordinary rejuvenator. In addition, reclaimed mixtures with the emulsified rejuvenator show similar moisture susceptibility to that with the ordinary rejuvenator. This study provides a feasible method to assess the workability effect of rejuvenators on reclaimed mixtures directly and recommends the use of an emulsified rejuvenator to improve the workability and high-temperature stability of reclaimed mixtures.